Examining low-income single-mother families' experiences with family benefit packages during and after the Great Recession in the United States - Yu-Ling Chang; Chi-Fang Wu (Journal of Risk and Financial Management, 2021)
The recent economic recession triggered by the global pandemic has renewed scholarly interest in the role of social welfare systems in supporting economically vulnerable families when they experience employment instability. This article unpacks the patterns of the cash and in-kind components of the monthly family benefit packages that US low-income single mothers accessed during and after the Great Recession. We used the 2008 Survey of Income and Program Participation and an innovative analytic procedure involving family benefit package plots, group-based trajectory modeling, and logistic regression modeling. We found that low-income single mothers more often used in-kind basic-needs packages and less often used packages that bundle a cash benefit or a childcare subsidy, regardless of their dynamic employment status. Our findings challenge the effectiveness of the US work-based welfare system in ensuring the economic security of economically vulnerable families and contribute to the policy discussions on unconditional basic income and President Biden's American Families Plan.
Keywords: 330; family benefit package; Great Recession; group-based trajectory modeling; single mothers in poverty; UpSet plots